IGU COMMISSION ON MARGINALIZATION, GLOBALIZATION, AND REGIONAL AND LOCAL RESPONSES, VIRTUAL CONFERENCE CLUJ-NAPOCA (ROMANIA), 9-10 AUGUST 2021 (Analele Universității București.Geografie, 2024)
The annual Conference of the Geographical International Union (IGU) – Commission on Marginalization, Globalization, and Regionaland Local Responses, had been postponed from 2020 to 2021 and was held online via Zoom in partnership with the Centre for Regional Geography of Babeş-Bolyai University, from Cluj-Napoca, Romania. The head of the organizing committee was Assoc. Prof. Raularian Rusu, and the local organizing team including Assoc. Prof. Titus Man, Dr. Ana-Maria Pop, Dr. Lelia Papp and Dr. Gheorghe Hognogi, all of Babeş-Bolyai University, Cluj-Napoca, Romania.